Anti-Thymocyte Globulin Prophylaxis in Patients With Hematological Malignancies Undergoing Allogeneic Hematopoietic Stem Cell Transplantation: An Updated Meta-Analysis - Yang, Xue; Li, Dongjun; Xie, Yao (Frontiers in Oncology, 2021)
Background: Anti-thymocyte globulin (ATG) prophylaxis reduces graft-versus-host disease (GVHD) incidence. This study aimed to explore the long-term efficacy of ATG and the influencing factors in patients undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT). Methods: PubMed, Embase, and Cochrane databases were searched for the relevant studies published up to August 2020. Data from randomized controlled trials (RCTs) on ATG prophylaxis for GVHD prevention in allo-HSCT patients were extracted for the meta-analysis. Results: A total of eight relevant RCTs (1348 patients) were included. The ATG use significantly reduced the incidence of grade III-IV aGVHD (P=0.001) and cGVHD (P<0.001). The ATG treatment significantly improved the GRFS (P<0.001). The immunosuppressive regimen (number and dose of immunosuppressives) was significantly reduced after adding ATG (P=0.005). Epstein-Barr virus (EBV) reactivation was significantly high in patients who received ATG (P=0.003). No significant differences were detected in relapses, overall survival (OS), relapse-free survival (RFS), and non-relapse mortality (NRM) between the ATG and no ATG groups. Subgroup analyses revealed that the donor type and ATG formulation might be the possible source of heterogeneity among studies. Meta-regression analysis showed that the cumulative dose of ATG did not affect GVHD, OS, relapse, RFS, and NRM. Conclusion: Although ATG had no significant effect on relapses, RFS, and NRM, it significantly reduced the occurrence and severity of GVHD and improved the GRFS and subsequent immunosuppression-free therapy of patients undergoing allo-HSCT.